Factors Influencing Malnutrition of Children Aged 24-60 Months Old in Flores Timur, Nusa Tenggara Timur - Betan, Yasinta; Hemchayat, Monthana; Wetasin, Kanokwan (Unnes Journal of Public Health, 2022)
Malnutrition remains a health problem in the world especially in developing countries such as Indonesia. This study aimed to determine factors influencing the nutritional status of children aged 24-60 months old in rural communities of Flores Timur, Nusa Tenggara Timur, Indonesia. This study was conducted in 5 villages in the rural community with a cross-sectional design. The total participant of this study was 250 mothers and children 24-60 months old. The participants were selected purposively. Data were collected using questionnaires of socio-demographic, dietary intakes, diseases, child care practices, and anthropometric measurement. Multivariate binary logistic regression was employed for the data analysis. Binary logistic regression revealed that energy intake (OR=8.99), protein intake (OR=6.95), the occurrence of infectious diseases (OR=6.45), the frequency of infectious diseases (OR=6.00), and age of introduction of complementary foods (OR=34.55) were significant factors that influence nutritional status in rural communities of Flores Timur, Indonesia. Based on these findings, health workers need to promote the appropriate time for giving the children complementary foods. Moreover, children who have experience of acute respiratory infection and/or diarrhea over the past six months should receive the appropriate intervention such as adequate dietary intake during illness to maintain nutritional status.